Women at the gates : gender and industry in Stalin's Russia - Goldman, Wendy Z. (Cambridge University Press, 2002)
"In the annals of industrialization, the Soviet experience is unique in its whirlwind rapidity. The vast transformations that shook western Europe over the centuries--proletarianization, industrialization, urbanization--were in the Soviet Union telescoped into a mere decade. The working class grew at an unprecedented rate, changing in size and social composition. Even more striking was the critical role of women: in no country of the world did they come to constitute such a significant part of the working class in so short a time. As women flooded industries traditionally dominated by men, they undercut strict hierarchies within the factories and forced male workers to reexamine their ideas about skill, 'masculine' and 'feminine' work, and the role of women in the workplace. The state's use of female labor was closely intertwined with the great upheavals of early Soviet history: accumulation of capital for the industrialization drive, the urban food crisis, collectivization, and peasant migration to the cities. Based on new Russian archival materials, Women at the Gates is the first social history of Soviet women workers in the 1930s. It is the story of a world remade, from above and from below, as planners 'regendered' the entire economy and women entered the ranks of waged labor in unprecedented numbers."--Publisher's description.